Salinity Stress Alters Nutrient Uptake and Causes the Damage of Root and Leaf Anatomy in Maize - Hasana, Rusdi; Miyake, Hiroshi (KnE Life Sciences, 2017)
Salinity is one of major problems in agriculture especially in arid and semiarid area due to causes the damage of many aspects in plant growth and development. This study observed root and leaf anatomy and nutrient uptake in maize plants exposed to salinity stress. Maize seedlings were placed in the plantation room under same temperature, humidity and light intensity conditions and were treated with 0 %, 1 %, 2 % and 3 % NaCl for 5 d. Anatomy of root and leaf were observed using scanning electron microscopy (SEM). Nutrient uptake was estimated by the content of trace elements of leaves. Trace element were quantified using inductively coupled plasma-mass spectrometry (ICP-MS), but chlorine was determined by an atomic absorption flame spectrometer. The results showed that salinity slightly damaged roots anatomy. Epidermis cells and parenchyma cells of cortex and pith were shrinkage in 2 % and 3 % NaCl-treated plants. Leaf anatomy showed mesophyll and bundle sheath cells which slightly suppressed. Meanwhile, chloroplasts content inside those cells were dramatically decreased. Anatomical damage of roots and leaves was accompanied by altering uptake of some trace elements. The contents of aluminum, calcium, iron, magnesium, sodium, chlorine, in NaCl-treated plants were higher than control. Otherwise, boron, potassium and phosphor were lower in NaCl-reated plants. The rest of trace elements were in comparable concentration. Keywords: maize; leaf; nutrient; root; salinity